The sacredness of human life : why an ancient Biblical vision is key to the world's future - Gushee, David P., 1962- (Grand Rapids, Mich. : William B. Eerdmans Pub. Co., 2013)
A comprehensive examination of the sacredness of human life, encompassing biblical roots, theological elaborations, historical cases, and contemporary ethical perspectives. Gushee argues that viewing human life as sacred is one of the most precious legacies of biblical faith-- albeit one that the church has too often failed to uphold.
Introduction -- What it means to say that human life is sacred -- The Old Testament and the sacredness of human life -- Jesus Christ, the New Testament, and the sacredness of human life -- The sacredness of life in early Christianity -- The fateful transition to Christendom -- Christendom divided against itself: three case studies -- Enlightenment transitions: natural rights, rule of law, and human dignity -- Nietzsche rejects the Christian God and Christian morality -- Desecrations: twentieth-century Nazi assaults on human life -- Honoring human life: twenty-first-century challenges -- The sacredness of God's creation -- Final words: For the church and its neighbors.
Includes bibliographical references (p. 424-440) and indexes.
Keywords: Theological anthropology -- Christianity; Dignity -- Religious aspects -- Christianity; Life -- Religious aspects -- Christianity; Apologetics; Christianity and culture; Apologetics; Christianity and culture; Dignity -- Religious aspects -- Christianity; Life -- Religious aspects -- Christianity; Theological anthropology -- Christianity